107PThe efficacy of adjuvant chemotherapy according to the risk classification of recurrence based on the systemic inflammatory markers in patients with colorectal cancer liver metastases. (24th November 2019) - Shibutani, M; Nagahara, H; Fukuoka, T; Iseki, Y; Hirakawa, K; Ohira, M
Abstract: Background: Although complete resection of colorectal cancer liver metastasis (CLM) is the only potentially curative treatment, surgery alone is not enough, as the recurrence rate after resection of CLM is high. Therefore, in clinical practice, adjuvant chemotherapy (AC) has been performed after resection of CLM. However, the evidence supporting the efficacy of AC after resection of CLM is not sufficient. Previous reports have noted that AC after resection of CLM is effective only in patients with a high risk of recurrence. The purpose of this study was to classify the risk of recurrence using systemic inflammatory markers, which have been reported to be associated with the clinical outcomes, and to evaluate the efficacy of AC according to the risk of recurrence. Methods: We retrospectively reviewed the medical records of 119 patients with CLM who underwent potentially curative surgery. The C-reactive protein-to-albumin ratio (CAR) was calculated from the blood samples by dividing the serum C-reactive protein level by the serum albumin level. The optimal cut-off value of the CAR was determined according to the ROC curve analysis, and then the patients were classified into the high- or low-CAR group. We examined the relationship between the CAR and the relapse-free survival (RFS) after resection of CLM and evaluated the efficacy of AC according to the risk of recurrence. Results: The cut-off value of the CAR was set at 0.0471 based on the ROC curve analysis. The RFS rates were significantly better in the low-CAR group than in the high-CAR group. The efficacy of AC after resection of CLM was not recognized in the low-CAR group (with a low risk of recurrence), whereas the RFS rates were significantly better for the patients who were treated with AC after resection of CLM in the high-CAR group (with a high risk of recurrence). Conclusions: The preoperative CAR was found to be useful as prognostic markers in patients with CLM who were treated with potentially curative resection. Furthermore, it was suggested that AC after resection of CLM may be effective for preventing recurrence in patients with high inflammatory markers who have a high risk of recurrence. Legal entity responsible for the study: Osaka City University. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.